Program Kepala Madrasah dan Implementasinya Dalam Peningkatan Aktivitas Guru Di Madrasah Aliyah Tarbiyatut Tholabah - Nur Hakim (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2020)
This study aims to determine the program carried out by the head of Madrasah in increasing teacher activity at Madrasah Aliyah Tarbiyatut Tholabah, how the implementation of Madrasah principal's programs in increasing teacher activity at Madrasah Aliyah Tarbiyatut Tholabah and the level of teacher activity in teaching at Madrasah Aliyah Tarhargatut Tholabah Kranji.The research approach used is qualitative research, while the research subjects are the head of the Madrasah, teachers and students of Madrasah Aliyah Tarbiyatut Tholabah. The research site is at Madrasah Aliyah Tarbiyatut Tholabah Kranji Paciran Lamongan. Data collection techniques using observation, interviews and documentation. data were analyzed by qualitative descriptive.The results of this study indicate that: 1. There are five programs carried out by Madrasah principals in an effort to increase teacher activity in teaching, namely: a). provide facilities, b). make the teacher absent, c). teacher training, d). socialization and empowerment of teachers e). carry out administrative sanctions, 2. Implementation of the madrasa principal program, namely: a). Provision of facilities is carried out at the beginning of the year and adjusts the needs of the learning process, b). Teacher attendance is made by the administrative field and is carried out by the picket teacher. c). Teacher training to improve the quality of teaching staff is carried out at the end of the school year before entering the new school year. d). The teacher socialization and empowerment program is carried out at the beginning of the academic year, among which is socialized, namely policies related to educators and madrasah, e). make teacher ordinances and their actions, take action for teachers who violate teacher rules, especially for those whose level of experience does not master the percentage target, which is below 70%. 3. The Madrasah principal program greatly affects the activity of teachers in teaching, from which the percentage of attendance was an average of 70% which increased to an average of 100%.